¿Debe tipificarse la corrupción privada en Ecuador? Análisis comparado del delito de corrupción en los negocios en España y de las normas del derecho de la competencia (Tema Central) - Olavarria, Francisco Eugenio (2016)
This article purpose is to analyze a widespread behavior within the world of business: private acts of corruption, also known as bribery in the corporate world. In general, we tend to focus our discussions with regard to public corruption,2 and we tend to be as rigid as we can with it, but contrary to this very little is usually done when it comes to only private corruption. Therefore, in this essay I will try to explain the Laws of Spain and Ecuador with regard to this matter, and I will try to illustrate the intimate and close relationship between corruption as a criminal offence and Antitrust Law. In that sense, I will explore precedents and leading cases from all over the world, the different types of offences and, finally, from the perspective of spanish unlawful act. I will set out my point of view with regard to which I consider the best way to deal with this matter, and lastly, I shall try to respond whether this kind of behaviors should be subjected to punishment by criminal law.